Pelatihan Dasar Literasi Digital bagi Guru SD Aisyiyah 1 Kauman Pagar Alam Menuju Pembelajaran Merdeka Berbasis Teknologi - Lestari, Reza; Rohani, Tri; Susanti, Novi; Aristya, Irma Sendy; Kalsum, Umi; Lismareni, Neni; Pratama, Yoga; Feriza, Firman; Nugroho, Sigit (Bengkulu Institute, 2025)
This Community Service activity aims to improve digital literacy understanding and skills among teachers at SD Aisyiyah 1 Kauman, Pagar Alam. Based on initial observations, it was found that most teachers had not yet optimally understood the use of digital technology in the learning process. Therefore, this training was designed using a participatory approach, actively involving teachers in each stage of the activity, including interactive lectures, workshops, and group discussions. The results of the training showed a significant improvement in the teachers’ understanding of digital literacy concepts, mastery of educational applications, and ability to design and implement technology-based learning. This activity is expected to serve as an initial step toward building a culture of digital learning in elementary schools and supporting educational transformation that is adaptive to the developments of the modern era.